A post-processing technique for removing 'irregular frequencies' and other issues in the results from BEM solvers. Issue 1 (June 2022) - Kelly, Thomas; Zabala, I˜naki, Yerai Pe˜na-Sanchez, Markel Penalba; Ringwood§, John V.; Henriques, Jo˜ao C. C.; Blanco, Jes´us M.
No abstract available